Pemenuhan Kebutuhan Paliatif pada Anak Neuroblastoma yang Mengalami Chemo-Brain : Laporan Kasus - Marbella Valemouren Saegaert; Tuti Asrianti Utami (Malahayati Nursing Journal, 2025)
ABSTRACT Neuroblastoma is a prevalent malignant solid tumor in pediatric populations, frequently diagnosed at an advanced stage. Chemotherapy serves as the principal treatment modality; however, it is associated with long-term adverse effects, including cognitive impairments collectively referred to as chemo-brain. This case report aims to elaborate on the palliative care needs and the nursing strategies employed to address the cognitive and holistic issues faced by children with neuroblastoma who exhibit symptoms of chemo-brain. A descriptive qualitative approach utilizing a case report design was applied. Data collection involved direct clinical observations, in-depth interviews with primary caregivers, and comprehensive analysis of nursing documentation for two pediatric patients diagnosed with stage IV neuroblastoma. Cognitive impairments due to chemo-brain were manifested through deficits in memory, communication, and behavioral functioning. Identified palliative needs encompassed physical (pain and constipation), psychological (emotional instability and anxiety), and social-spiritual domains. Nursing interventions, including play therapy, relaxation techniques, and family-centered care, were instrumental in addressing these multidimensional needs. The implementation of a comprehensive, multidisciplinary, and family-involved palliative care approach significantly contributes to enhancing the quality of life in pediatric patients experiencing chemo-brain secondary to neuroblastoma. Keyword: Chemo-brain, Neuroblastoma, Pediatric Palliative Care, Cognitive Impairment, Holistic Nursing.  ABSTRAK Neuroblastoma merupakan salah satu jenis tumor padat yang paling umum ditemukan pada populasi anak dan sering kali terdiagnosis pada stadium lanjut. Kemoterapi sebagai terapi utama dapat menyebabkan efek samping jangka panjang berupa gangguan fungsi kognitif yang dikenal dengan istilah chemo-brain. Laporan kasus ini bertujuan untuk menguraikan kebutuhan paliatif yang dialami oleh anak dengan neuroblastoma yang mengalami chemo-brain serta strategi keperawatan yang digunakan untuk memenuhi kebutuhan tersebut secara menyeluruh. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi klinis langsung, wawancara mendalam dengan orang tua, dan telaah dokumentasi keperawatan pada dua anak yang didiagnosis neuroblastoma stadium IV. Gangguan kognitif yang dialami anak mencakup penurunan memori, kemampuan komunikasi, dan fungsi perilaku. Kebutuhan paliatif yang teridentifikasi meliputi aspek fisik (nyeri dan konstipasi), psikologis (emosi labil dan kecemasan), serta sosial dan spiritual. Intervensi keperawatan berupa terapi bermain, teknik relaksasi, dan perawatan berpusat pada keluarga terbukti berkontribusi dalam pemenuhan kebutuhan tersebut. Pendekatan paliatif yang menyeluruh, melibatkan kolaborasi multidisiplin dan peran aktif keluarga, terbukti efektif dalam meningkatkan kualitas hidup anak dengan chemo-brain akibat terapi kanker. Kata Kunci: Chemo-brain, Neuroblastoma, Paliatif Anak, Gangguan Kognitif, Keperawatan Holistik